(untitled) (Homiletic, 2022)
The performative implications of the gospel have been the focus of intense homiletical reflection. These reflections explore avenues through which the “what” of the gospel shapes the “how” of its proclamation. Yet one feature of the gospel that has received little attention is the connection between the gospel’s inherent vulnerability and how that vulnerability should shape sermonic performance. This paper considers what possible impact the vulnerability intrinsic to the gospel, as good news, should have on one’s preaching performance and the potential implications of this connection. Drawing on speech-act theory and a theological understanding of the gospel as “good news,” this paper argues sermonic performance that mirrors the gospel’s nonviolent epistemology is a necessary condition for gospel speech. It suggests performative distance as one strategy for meeting this condition and that such a strategy reveals the potential significance of patience as a homiletically significant virtue.